The Study of the Impact of Macroeconomic Stability and Crisis Effects on MSMEs Financing of Sharia Commercial Banks in Indonesia - Putri, Amila Zamzabila; Musthofa, Muhammad Wakhid (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
The COVID-19 pandemic epidemic that the Indonesian state experienced caused a crisis in the economy that has negatively impacted the country's economy. 2020 has seen a slowdown in the rate of economic growth, which has made it more difficult for MSMEs operations to get bank capital loans. Every year, sharia commercial banks have allocated less finance to MSMEs. Because of this, many MSMEs encounter a capital shortage during their production process. Due to this, the aim of this study is to investigate how macroeconomic variables”interest rates, inflation, and the impact of the economic crisis”act as financial factors and how much of the channel sharia commercial banks can finance MSMEs. sharia commercial banks that are registered with the Financial Services Authority (OJK) between 2019 and 2021 are the object of this study. This study uses secondary data in a quantitative research. In this study, data analytic techniques included multiple linear regression analysis, hypothesis testing, and classical assumption testing. The findings indicate that the interest rate variable and the effects of the economic crisis had a significant negative impact on the MSMEs financing. On the other hand, the MSMEs finance was significantly positively impacted by the inflation variable.